Financial law and financial science in Russian Federation and Czech Republic (comparative research) - M. Karfíkova; E. V. Chernikova (Правоприменение)
The methodology. Comparative legal, historical and analytical scientific methods were used. The main results, scope of application. Formation of financial-legal theory in both countries took place under the circumstances of political changes. In relation to the Czechoslovak Republic, the attention is focused on the period from the formation of the Czechoslovak Republic in 1918 to the formation of the Czech Republic in 1993, and the main emphasis is made on the period of the 21st century. Periodization of financial law and financial science, and also the system of financial law considers the teaching of financial law and financial science at the Faculty of Law, Charles University. The study also characterizes the process of development of financial law and financial science in pre-revolutionary Russia, highlights the Soviet period of development of financial law, focuses on the problems of development of modern financial law. Periodization of financial law, as well as the system of financial law, are presented from the perspective of teaching of the subject of financial law at the faculties of law. The authors suppose that the modern system of financial law and financial science has retained the original division into two parts, general and specific. All sub-branches of the special part of financial law may be divided into three main blocks: (1) sub-branches of the fiscal part of financial law; (2) sub-branches of the non-fiscal part of financial law; common sub-branches of the non-fiscal part of financial law.Conclusions. The hypothesis about the unity of the principles of financial law and financial science, and public finance as the main category, as well as about the independence of this branch of public law was confirmed during the study. Due to the growing volume of legal regulation in both countries, the historical division of the financial law system is not enough, there is an extensive fragmentation of division in the financial law system. We are observing the emergence of new sub-branches, which are likely to tend to the formation of new branches.